2019
DOI: 10.1055/s-0039-1696640
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Weight Gain and Pregnancy Outcomes among Nulliparous Women

Abstract: Objective To determine the association between total gestational weight gain and perinatal outcomes. Study Design Data from the Nulliparous Pregnancy Outcomes Study: Monitoring Mothers-To-Be (NuMoM2b) study were used. Total gestational weight gain was categorized as inadequate, adequate, or excessive based on the 2009 Institute of Medicine guidelines. Outcomes examined included hypertensive disorders of pregnancy, mode of delivery, shoulder dystocia, large for gestational age or small for-gestational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 38 publications
5
25
1
1
Order By: Relevance
“…In a recent study among nulliparous American women with singleton pregnancies, Dude et al showed that GWG rates in the second and third trimester below and above IOM recommendations were associated with higher odds of SGA (AOR = 1.37, 95% CI: 1.08, 1.73) and LGA infants at birth (AOR = 1.34, 95% CI: 1.01, 1.79), respectively. Although the study did not find any link between low weight gain and LGA, unlike us, they found that excessive rate of weight gain significantly reduced the risk of SGA babies [ 40 ]. A retrospective chart analysis of data from 29,861 women in 25 U.S. hospitals found higher odds of macrosomia among women with rates of GWG above IOM recommendations (AOR = 2.66, 95% CI: 2.03, 3.48) but did not find any association with weight gain below the recommendations [ 5 ].…”
Section: Discussionmentioning
confidence: 72%
“…In a recent study among nulliparous American women with singleton pregnancies, Dude et al showed that GWG rates in the second and third trimester below and above IOM recommendations were associated with higher odds of SGA (AOR = 1.37, 95% CI: 1.08, 1.73) and LGA infants at birth (AOR = 1.34, 95% CI: 1.01, 1.79), respectively. Although the study did not find any link between low weight gain and LGA, unlike us, they found that excessive rate of weight gain significantly reduced the risk of SGA babies [ 40 ]. A retrospective chart analysis of data from 29,861 women in 25 U.S. hospitals found higher odds of macrosomia among women with rates of GWG above IOM recommendations (AOR = 2.66, 95% CI: 2.03, 3.48) but did not find any association with weight gain below the recommendations [ 5 ].…”
Section: Discussionmentioning
confidence: 72%
“…Excessive weight gain in this period is common (about 50% of pregnant women) [ 9 ] and is consistently associated with adverse fetal and child’s metabolic and neurocognitive outcomes [ 11 , 12 ]. Moreover, a higher risk for macrosomia, newborns large for gestational age, cesarean delivery, and maternal hypertension alterations have been reported [ 13 , 14 ]. Obesity is common during pregnancy, affecting both the mother and her offspring [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sartorelli et al [ 23 ] also showed that women classified into the highest tertile of UPFs intake had a three times higher chance of obesity when compared to women with the lowest intake of these foods. Thus, monitoring this trend in pregnant women should be an important healthcare concern objective since excessive GWG is associated with greater chances of hypertensive disorders, cesarean delivery, and LGA newborns [ 105 , 106 , 107 ], and a strong predictor of postpartum weight retention, contributing to obesity in later life [ 108 , 109 ].…”
Section: Discussionmentioning
confidence: 99%